Perlindungan Hukum Konflik Batas Wilayah Sipadan Dan Ligitan Dalam Hukum Internasional - Seri Mughni Sulubara; Oni Tri Asri; Maulida Maulida; Sinta Amelia; Hasma Yanti; Namira Simah Bengi; Maula fitri; Zikri Yandi; M Fizza Anggara; Diana Juwita; Fachrul Razi; Niswatul Khaira; Laya Shafura; Nurkhalisah Nurkhalisah (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The dispute between Indonesia and Malaysia over the islands of Sipadan and Ligitan continued throughout the years until 1997. The issue of Sipadan and Ligitan islands was resolved by international law through the International Court of Justice. The two islands located in the middle of Indonesia, precisely in the Makassar Strait, were finally won by the Malaysian side on December 17, 2002. The theory used in this research is the theory of legal protection. The theory of legal protection is very relevant to the research made here, because there is a need for legal protection regarding territorial boundaries in the territorial sovereignty of the State of Indonesia. The research method used regarding international legal protection of the Sipadan-Ligitan island dispute is carried out by means of qualitative descriptive research. The technique or instrument of data collection used is library research by studying various books as literature, official documents, laws and regulations, results of previous research, and other literature sources related to the problems studied. The decision of the international court on December 17, 2002 in its decision gave sovereignty over the islands of Sipadan and Ligitan to Malaysia, the international court declared Malaysia as the most entitled party to the two islands based on three main statements that were used as the basis for claims by both countries.